Stability of Bituminous Emulsion Induced by Waste Based Bio-Surfactant - Michele Porto; Paolino Caputo; Abraham A. Abe; Valeria Loise; Cesare Oliviero Rossi (Applied Sciences, 2021)
In the asphalt industry, bituminous emulsions are widely used in road pavement operations and in building/construction processes such as cold mix asphalt and waterproofing processes, respectively. A very important fact to keep in mind is that not all types of bitumen are suitable for the realization of bituminous emulsions. This is largely due to the variation in their chemical nature and the different cracking processes carried out on the bitumen during the fractional distillation process in the petroleum industry. The objective of this study is to identify the underlying causes of the non-emulsionability of bitumen using Nuclear Magnetic Resonance (NMR) and Dynamic Shear Rheology (DSR) analysis. NMR analysis aims at identifying the fundamental chemical components that are responsible for the emulsionability of the bitumen binder and how important their role is in this phenomenon. On the other hand, the DSR analysis is aimed at determining if the rheological (viscoelastic) behavior of bitumen is implicated in its emulsionability. The indications gotten from the data produced by these techniques, enable us as soon as the analyzed bitumen is deemed non-emulsionable to identify what type of additive can be used to modify the bitumen and alleviate its non-emulsionability until a point where its chemical components become ideal for the realization of bituminous emulsions. In this research work, a model bitumen (labelled as Cimar) which is known for its excellently high emulsionability in the production of anionic bituminous emulsions was used as the reference sample. Two bitumens (labelled as Adriatica and Alma) which from preliminary testing were deemed non-emulsionable were alongside the additives selected and subjected to the aforementioned techniques for analysis on their emulsionability. The NMR data obtained allowed the identification of the chemical nature of the components of the analyzed bitumens and the design of the right additive which improves the bitumen and makes it suitable for the preparation of emulsions. In addition to these, a largely uncommon however effective method of acid number determination of bitumen gave indications on an underlying factor which largely influences the emulsionability of bitumen. An aliphatic and an aromatic surfactant were identified thanks to the spectroscopic findings in this study.